Risk stratification to predict pain during unsedated colonoscopy: results of a multicenter cohort study - Holme, Øyvind; Bretthauer, Michael; de Lange, Thomas; Seip, Birgitte; Huppertz-Hauss, Gert; Høie, Ole; Sandvei, Per; Ystrøm, Carl Magnus; Hoff, Geir (Endoscopy, 2013)
Background and study aims: Colonoscopy without sedation has several advantages over sedated colonoscopy, but a considerable proportion of patients experience pain. The aim of this study was to develop a risk stratification model of pre-examination risk factors to enable targeted sedation during colonoscopy. Patients and methods: Between October 2011 and January 2012, consecutive outpatients who were willing to start colonoscopy without sedation at 11 Norwegian centers were prospectively recruited. Patients recorded pain on a validated 4-point scale (none, slight, moderate, or severe pain). Potential risk factors for a painful procedure (defined as moderate or severe pain) were evaluated using multivariate logistic regression analyses, and the area under the receiver operating characteristics curve (AUROC) was calculated to assess the discriminatory ability of the derived model. Results: A total of 1198 patients (635 men and 563 women) were included. Seven independent, pre-procedural risk factors for patient pain were identified: female sex, age < 40 years, previous abdominal surgery, abdominal pain as indication for colonoscopy, anticipation of pain, previous painful colonoscopy, and a history of diverticulitis. In patients with 0, 1, 2, or ≥ 3 risk factors, a painful colonoscopy was experienced by 35 %, 43 %, 52 %, and 63 % of women and 18 %, 24 %, 35 %, and 63 % of men, respectively. The model showed modest discrimination abilities (AUROC = 0.69).Conclusion: Female sex was a strong risk factor for pain during colonoscopy, and sedation or analgesia should be considered for all women prior to colonoscopy. For male patients, the presence of multiple risk factors should encourage the endoscopist to offer sedation.